Intermediate-temperature electrochemical performance of a polycrystalline PrBaCo2O5+d cathode on samarium-doped ceria electrolyte - Chen, D.; Ran, R.; Zhang, K.; Wang, J.; Shao, Zongping (Elsevier SA, 2009)
A-site cation-ordered PrBaCo2O5+d (PrBC) double perovskite oxide was synthesized and evaluated as the cathode of an intermediate-temperature solid-oxide fuel cell (IT-SOFC) on a samarium-doped ceria (SDC) electrolyte. The phase reaction between PrBC and SDC was weak even at 1100 °C. The oxygen reduction mechanism was investigated by electrochemical impedance spectroscopy characterization. Over the intermediate-temperature range of 450-700 °C, the electrode polarization resistance was mainly contributed from oxygen-ion transfer through the electrode-electrolyte interface and electron charge transfer over the electrode surface. An area-specific resistance as low as ~0.4 O cm2 was measured at 600 °C in air, based on symmetric cell test. A thin-film SDC electrolyte fuel cell with PrBC cathode was fabricated which delivered attractive peak power densities of 620 and 165 mW cm-2 at 600 and 450 °C, respectively. © 2008 Elsevier B.V. All rights reserved.